THE HISTORY OF THE CREATION OF THE NOVEL "THE GREAT KINGDOM" (Academia Science Repository, 2023)
Among the historical figures who left a worthy name in our history during the years of independence, the artistic embodiment of the image of Amir Temurga took on a unique tradition in our literature. An artistic system of works dedicated to Amir Temur was created in almost all literary genres. M. Ali's novel "The Great Kingdom", A. Oripov's poetic drama "Sahibgiron", T. Nizam's "Avvalu end", A. Eshanov's poems "One Moony Night in Samarkand", G. Karim's dramatic story "Sahibgiron and Alloma" were created. In A. Oripov's poetic drama "Sahibqiron", Amir Temur's life path, his entire activity was put on the scales of universal dimensions and tried to be artistically depicted. Historically, the geography of Amir Temur's activity is very wide. The problems that occupied him and tried to solve them are also innumerable. Jahangir's character is also colorful. Abdulla Oripov was able to find the most necessary and the most meaningful of these vastnesses, problems, and colors, and he was able to clearly and succinctly reflect them in moral and philosophical terms.